Conceptual Model of Computer Utilization in 21st Century Science Learning: Grounded Theory-Informed Literature Review - Lathif, Yuniar Fahmi; Prasetya, Muhammad Gibran Alif; Yasin, Ahmad Alfian Risydan (International Journal Education and Computer Studies (IJECS), 2026)
The use of computers in science education continues to be dominated by technocentric approaches that treat technology as an end in itself rather than a means of learning. This research aims to deconstruct prevailing research trends and construct a new conceptual model explaining how computers can be used effectively in 21st-century science learning. Using a Systematic Literature Review (SLR) design with the PRISMA 2020 protocol, this study selects and analyzes high-quality articles from reputable databases. Data analysis followed a Grounded Theory-Informed approach to extract recurring patterns and build theoretical propositions inductively. Three fundamental dimensions emerged to form the new conceptual model: (1) Teacher Agency and Ecosystem Readiness as determinant input variables that precede hardware availability; (2) Hybrid Pedagogy and Distributed Scaffolding as the core process mechanism that bridges physical and digital learning experiences; and (3) Methodological Adaptability as a moderator variable that adjusts instructional strategies to the complexity level of the subject matter. This study concludes that technology effectiveness is not deterministic — it depends on an adaptive pedagogical ecosystem built around teacher capacity and contextual design. These findings carry strategic implications for curriculum developers and policymakers: prioritize discipline-specific teacher professional development, and design learning environments that pair virtual simulations with real-world experiments.